2018
DOI: 10.1080/09553002.2018.1518612
|View full text |Cite
|
Sign up to set email alerts
|

Relation between DNA double-strand breaks and energy spectra of secondary electrons produced by different X-ray energies

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Errors correspond to the standard deviation (SD) of the mean over 10 batches. [30]. As can be observed, the σ rel z decreases when the dose increases.…”
Section: Yields Of Dsb/gy/gbp and Dsb Complexitymentioning
confidence: 61%
See 3 more Smart Citations
“…Errors correspond to the standard deviation (SD) of the mean over 10 batches. [30]. As can be observed, the σ rel z decreases when the dose increases.…”
Section: Yields Of Dsb/gy/gbp and Dsb Complexitymentioning
confidence: 61%
“…4(see 4.3.1.) in the irradiated cell population for the three photon energy spectra as a function of the simulated doses 0.25 Gy, 0.5 Gy, 1 Gy, and 2 Gy, as used in the experiments [30]. As can be observed, the σ decreases when the dose increases.…”
Section: Microdosimetric Calculationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Researchers have considered the impacts of low-dose radiation, given as a single dose or fractionated or prolonged over time, with regard to altering cancer progression or resolution as well as their impacts on the systemic immune system [23] .It was found that low-dose radiation increases cellular antioxidant activity; facilitates DNA damage repair; reduces malignant transformation and mutagenesis, and stimulates immune surveillance [24]. The cell nucleus and DNA are susceptible to several stressors[25, 26,27,28] and can be greatly harmed with relatively low doses of ionizing radiation [29,30]. As adverse effects of ionizing radiation on (cancer) cells are mainly mediated by fragmentation of nuclear chromatin via inserting double strand breaks (DSBs) into the DNA molecule [31].…”
Section: Discussionmentioning
confidence: 99%